Determination Study of Measurement Uncertainty On Crude Palm Oil (CPO) Using Several Chemical Analysis Methods - Chairuddin (Talenta Publisher, 2020)
The measurement uncertainty on crude palm oil (CPO) for the determination of free fatty acid using the neutralization titration method base AOCS Ca5a – 40, and the determination of the Fe2+ using the spectrophotometric method have been studied. The process of uncertainty estimation is based on specifying measurand, identifying uncertainty sources, quantifying uncertainty using type A (by the statistical analysis of series of observations) and type B (by the other statistical analysis of series observations) evaluation of uncertainty, then converting them to deviation standards, and the last step was to calculate and combine the uncertainty standard and uncertainty expanded. Spreadsheet software MS Exel 2007 based on Kragten spreadsheet uncertainty calculation method was used to simplify the calculation of the combined standard uncertainty. The combined standard uncertainty was multiplied with a coverage factor of 2, and the expanded uncertainty for analysis determination of free fatty acid using the neutralization titration method based on AOCS Ca5a–40 with a concentration of 0.1612 mol/L in the sample solution was ±0.0002 mol/L. Whereas the expanded uncertainty for the determination of Fe2+ using a spectrophotometric method with a concentration of 0.131 mg/L in the sample solution was ±0.083 mg/L and calculated using a coverage factor of 2.14.